Perspectives for a Framework to Understand Aril Initiation and Development - Silveira, Sylvia R.; Dornelas, Marcelo C.; Martinelli, Adriana P. (Frontiers in Plant Science, 2016)
A differentiated structure called “aril” has been described in seeds of several plant species during the course of evolution and might be considered as a supernumerary integument. Besides its ecological function in seed dispersal, the structure also represents a relevant character for systematic classification and exhibits important properties that impart agronomic value in certain species. Little is known about the molecular pathways underlying this morphological innovation because it is absent in currently used model species. A remarkable feature of the seeds of Passiflora species is the presence of a conspicuous aril. This genus is known for the ornamental, medicinal, and food values of its species. In view of the molecular resources and tools available for some Passiflora species, we highlight the potential of these species as models for developmental studies of the aril.